2006
DOI: 10.1088/0268-1242/21/4/007
|View full text |Cite
|
Sign up to set email alerts
|

Thin films of arsenic sulfide by chemical deposition and formation of InAs

Abstract: We report a method for obtaining thin films of arsenic sulfide by chemical bath deposition and the subsequent formation of InAs by heating the films with a vacuum-deposited coating of In. X-ray diffraction (XRD) studies have shown that the thin film deposited from chemical baths of pH ∼2, prepared by mixing aqueous acidic solutions of As(III) with sodium thiosulfate, is a composite film of crystalline As 2 O 3 and As 2 S 3 , with the incorporation of sulfur. When heated at 150-250 • C, the As 2 O 3 component t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…SEM images (not shown) revealed that the film was badly damaged, but EDS measurements showed that at least some As and S were still left. Our results are in agreement with literature where sublimation upon annealing at 150-250 °C has been reported for films deposited by thermal evaporation 28 and by chemical bath deposition 29 . Furthermore, As 2 S 3 is known to be very reluctant to crystallization 30 .…”
Section: B Film Propertiessupporting
confidence: 93%
“…SEM images (not shown) revealed that the film was badly damaged, but EDS measurements showed that at least some As and S were still left. Our results are in agreement with literature where sublimation upon annealing at 150-250 °C has been reported for films deposited by thermal evaporation 28 and by chemical bath deposition 29 . Furthermore, As 2 S 3 is known to be very reluctant to crystallization 30 .…”
Section: B Film Propertiessupporting
confidence: 93%
“…where d is the lm thickness, T is the transmittance and R is the reectance of the investigated samples. [26][27][28][29] The thickness of the deposed thin lms was determined with a MII-4 interference microscope (Linnik) with an error #0.01 mm using the multiple-beam Fizeau fringe method. 30 The thickness of the thin lms was about 258 nm.…”
Section: Characterization Methodsmentioning
confidence: 99%
“…The optical band gap energy, E g , of the Cu-doped ZnO NPs dispersed in ethylic alcohol and deposited as thin films on Soda lima glass substrates by spin-coating technique (at 2000 rpm) was estimated from the fundamental absorption edge in their optical transmittance and reflectance spectra, acquired in air at room temperature with a Perkin Elmer Lambda 35 spectrometer, at normal incidence, in the 200–1100 nm spectral range. For E g evaluation, the absorption coefficient was calculated using the following Equation (1) [ 40 ]: where d is the film thickness, T is the transmittance and R reflectance of the ZnO 1D nanostructured thin films. The E g values were calculated from the dependence of absorption coefficient vs. the photon energy, hν, based on the following Equation (2) [ 19 , 20 , 21 , 41 ]: where A is a parameter that depends on the transition probability.…”
Section: Methodsmentioning
confidence: 99%